2018
DOI: 10.1007/s10548-018-0654-7
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Processing of Aesthetic Information in the Human Brain Revealed by Neural Adaptation Paradigm

Abstract: Some researchers in aesthetics assume visual features related to aesthetic perception (e.g. golden ratio and symmetry) commonly embedded in masterpieces. If this is true, an intriguing hypothesis is that the human brain has neural circuitry specialized for the processing of visual beauty. We presently tested this hypothesis by combining a neuroimaging technique with the repetition suppression (RS) paradigm. Subjects (non-experts in art) viewed two images of sculptures sequentially presented. Some sculptures ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…This connectivity might reflect the dynamic process for the visual and aesthetic properties of faces. In 2018, Iwasaki studied the aesthetic perception of visual features by comparing sculptures obeyed the golden ration (canonical sculpture) with sculptures in which golden ratio was impaired (deformed sculpture) [95]. They found that the connectivity between the right occipital-temporal region and the right parietal region was correlated with the presentation of canonical sculptures but not for deformed sculptures, suggesting a neural pathway between these regions during the processing for aesthetic information.…”
Section: Brain Functional Connectivity and Brain Network In Neuroaesmentioning
confidence: 99%
“…This connectivity might reflect the dynamic process for the visual and aesthetic properties of faces. In 2018, Iwasaki studied the aesthetic perception of visual features by comparing sculptures obeyed the golden ration (canonical sculpture) with sculptures in which golden ratio was impaired (deformed sculpture) [95]. They found that the connectivity between the right occipital-temporal region and the right parietal region was correlated with the presentation of canonical sculptures but not for deformed sculptures, suggesting a neural pathway between these regions during the processing for aesthetic information.…”
Section: Brain Functional Connectivity and Brain Network In Neuroaesmentioning
confidence: 99%